Optimum location and distribution of insulation layers on building walls with various orientations - Ozel, M.; Pihtili, K. (Pergamon-Elsevier Science Ltd, 2007)
In this study, to determine optimum location and distribution of insulation in a wall, an analysis was made of 12 different wall configurations with different configurations of insulation layers. The investigation was carried out by using an implicit finite difference method for multilayer walls during typical summer and winter days in Elazig, Turkey. For this purpose, the location of insulation layers was varied across the wall thickness for each configuration while the masonry thickness and the total insulation thickness were held constant. The optimum location of insulation for the configurations analysed was obtained from consideration of time lag and decrement factor for various wall orientations in both summer and winter conditions. Results showed that the best thermal performance was obtained in the case that one of three equal pieces insulation layers was placed in the outdoor surface of wall, the second piece of insulation was placed in the middle of wall and third piece of insulation was placed in the indoor surface of wall. Furthermore, it was found that equal thicknesses of insulation layers placed in the indoor and outdoor surface of wall was better than different thicknesses from the point of view of maximum time lag and minimum decrement factor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: location and distribution of insulation; orientations of wall; time lag; decrement factor